PERANAN UDARA PANTAI TERHADAP KOROSI BALING-BALING HELIKOPTER HUGHES-300C - Aryananta Lufti; Budi Harjanto; Frangky Silitonga (JURNAL MEKANIKASISTA, 2022)
The purpose of this study includes three important things, including the effect of coastal air on the coastal environment, corrosion rate, and hardness of the Heli Hughes-300C propeller. The method used is a qualitative approach using a corrosion rate measuring device, namely Cell 3 Electrodes with liquid seawater from Maron Beach, Semarang as a corrosion medium. Each specimen will be tested for composition, calculated corrosion rate and tested for hardness. Specimen Making: Specimen making for this test was carried out by taking part of the Hughes 300C Helicopter propeller and then forming it to the size of the tube. Composition test: The composition test was carried out at the UGM Engineering Materials Laboratory using a spectrometer. Based on the results above, it was found that the Hughes 300C propeller after being corroded had a higher hardness value (average VHN 135.75kgf/mm2) compared to the one before it was corroded (average VHN 128.79 kgf/mm2). These results indicate that the propeller after being corroded will be more rigid, where there is a shift in the hardness standard value of the propeller. A brittle propeller will break more easily when it hits a hard impact in the air compared to a low-friction propeller due to the movement of the flap on the propeller when the blade angle changes and the push from the wind when flying.